Differential item functioning in Malaysian Generic Skills Instrument (MyGSI) - Siti Rahayah Ariffin,; Rodiah idris,; Noriah Mohd Ishak, (penerbit ukm, 2010)
Apart from good academic performance, generic skills are necessary for students in order to be more successful and to excel as practitioners in academic fields, work and careers. The development of the Malaysian Generic Skills Instrument(MyGSI) is based on the Malaysian Qualification Framework which applies cognitive, behaviorism and social theories. The purpose of this study is to detect Differential Item Functioning (DIF) in MyGSI based on gender, types of program and race. Data was obtained from 1,262 undergraduate students randomly chosen from 12 faculties at Universiti Kebangsaan Malaysia (UKM). The MyGSI used consists of 13 constructs and 102 items on a 4-point likert scale. In addition, Winsteps software version 3.64.2 has been used for data analysis. The findings had detected five misfitting items; one item was distinguished as DIF based on types of programme and 12 items were detected as DIF based on race. The final analysis using the Rasch’s model has dropped 15 items and maintained 87 items that were legitimate and reliable to gauge 13 constructs in MyGSI. This MyGSI, free from DIF, could be used to obtain Higher Learning Institutions(HLI) students’ profile in a justly manner. In short, it could be used as an indicator to increase students’ generic skills during their study in the university.